Endocrine Control of Fetal Growth, the Delivery Process, and the Physiology of Childbirth - Maelissa, Merlin Margreth; Siddiq, Amillia; Islamy, Nurul; Puspitasari, Maya Khaerunnisa; Lumentut, Anastasia Mariane; Wirawan, Wahyudi (Newinera Publisher, 2025)
Childbirth is a complex physiological process characterized by the expulsion of the fetus from the uterus, marked by uterine contractions and cervical changes. The timing of labor is crucial for favorable pregnancy outcomes and is regulated by the neuroendocrine maturation of the fetus. Hormones like estrogen, progesterone, and human placental lactogen play key roles in fetal growth regulation, with fluctuations influencing birth weight and placental development. Progesterone inhibits labor by relaxing the uterus, while estrogen promotes labor by stimulating uterine contractions and cervical changes. The transition from uterine quiescence to active labor involves multiple stages, from myometrial relaxation to enhanced contractility. Labor progresses through phases, starting with quiescence, followed by the onset of rhythmic contractions, active labor, and concluding with involution. Uterine stretching and the role of fetal lung maturation also contribute to labor initiation, as fetal lung surfactant activates macrophages, leading to inflammation and progesterone withdrawal. This process synchronizes labor timing with fetal lung development. In conclusion, labor is influenced by a combination of endocrine and mechanical factors, including prostaglandins, cytokines, and hormones such as oxytocin and CRH. Proper endocrine regulation ensures timely labor, while disruptions in this system, such as premature or prolonged pregnancies, can lead to increased fetal morbidity and mortality.